2017
DOI: 10.1007/978-981-10-4397-0_7
|View full text |Cite
|
Sign up to set email alerts
|

Dual Behavior of Exosomes in Septic Cardiomyopathy

Abstract: Sepsis is one of the main causes of ICU hospitalization worldwide, with a high mortality rate, and is associated with a large number of comorbidities. One of the main comorbidities associated with sepsis is septic cardiomyopathy. This process occurs mainly due to mechanisms of damage in the cardiovascular system that will lead to changes in cardiovascular physiology, such as decreased Ca response, mitochondrial dysfunction and decreased β-adrenergic receptor response. Within this process the exosomes play an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…Exosomes are small cell-derived vesicles originate from leukocytes, platelets and dendritic cells, etc. (Monteiro et al, 2017). Exosomes are a double-edged sword that can protect and cause SCM.…”
Section: The Effects Of Exosomes On Cardiac Function In Sepsismentioning
confidence: 99%
See 4 more Smart Citations
“…Exosomes are small cell-derived vesicles originate from leukocytes, platelets and dendritic cells, etc. (Monteiro et al, 2017). Exosomes are a double-edged sword that can protect and cause SCM.…”
Section: The Effects Of Exosomes On Cardiac Function In Sepsismentioning
confidence: 99%
“…Exosomes are a double-edged sword that can protect and cause SCM. The roles of exosomes in SCM is mainly considered from two mechanisms that are exosomal nicotinamide adenine dinucleotide phosphate (NADPH) and microRNA-223 (Monteiro et al, 2017). A study has shown that exosomes can induce vascular apoptosis and myocardial dysfunction by the mechanisms that are related to inflammation and oxidative stress (Real et al, 2018).…”
Section: The Effects Of Exosomes On Cardiac Function In Sepsismentioning
confidence: 99%
See 3 more Smart Citations